PENGARUH VARIABEL ASET LANCAR, DEBT TO TOTAL ASSETS, UMUR, DAN JUMLAH ANGGOTA TERHADAP RENTABILITAS EKONOMI DI KOPERASI SIMPAN PINJAM DAN KOPERASI KREDIT DI KECAMATAN BULELENG, KABUPATEN BULELENG: SEBUAH PEMODELAN EKONOMETRIKA - Agus Ardiana, Putu; Kartini Eka Sari, Luh (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 5 No 2 (2010), 2010)
This paper aims to investigate independent variables affecting profitabilityof cooperatives in Buleleng, Bali proxied by a ratio of earnings and total assetsthrough an econometric modeling. We initially identified 18 variables affectingthe ratio but we then dropped a number of independent variables insignificantlyaffecting the ratio. Conducting 15 modelling, the last econometric model is aBLUE (Best Linear Unbiased Estimators) model implying that the model has noclassical assumptions problems at all. The BLUE model suggests thatindependent variables affecting profitability of cooperatives in Buleleng, Bali arecurrent assets, debt to total assets, age, and the number of member ofcooperatives.
Keywords: Cooperatives, Profitability, Current Assets, Debt to Total Assets, Age, and The Number of Members of Cooperatives